APAKAH GEN Z BERMINAT UNTUK MENGGUNAKAN DOMPET DIGITAL SECARA BERKELANJUTAN? - Nandita Rakhmad; Akhmad Saebani (Bajang Institute, 2024)
This research is a quantitative study that aims to determine the effect of ease of use, perceived usefulness, and trust on interest in continued use of e-wallet systems. This study uses Generation Z as the sample. Determination of the sample size was carried out using the Malhotra formula and sample selection was carried out using accidental sampling techniques which resulted in a sample size of 150 respondents. Hypothesis testing in this study uses multiple linear regression analysis with the help of statistical tools in the form of STATA and the significance level used is 5% (0.05). The results obtained from the tests carried out are ease of use, perceived usefulness, and trust have a significant influence on interest in continued use of the digital wallet system